Towards an effective approach to teaching reading skills in the intermediate phase : a case study of rural primary school - Ramalepe, Mammoni Petrus (My University, 2018)
Despite the introduction of a number of educational policies and measures (for example, the Foundation for Learning Campaign, the National Reading Strategy (2008), Integrated National Literacy and Numeracy Strategy (INLNS) (Department of Basic Education, 2011), Certificate in Primary English Language Teaching (CiPELT)) in 2012-13 to increase the quality of education during and over twenty three years of democracy in South Africa, there are still problems with regard to reading levels of rural South African learners in the intermediate phase. The in/ability to read at grade level, still persist even after the introduction of teaching of English as a subject from Grade 1 in all schools as prescribed by CAPS. Available literature on reading in/abilities in South African schools concedes that the problem lies in the primary schools. The aim of this study was to investigate and determine an effective approach to teaching reading skills in the intermediate phase. I employed convergent parallel design as both the quantitative and qualitative strands were used concurrently and equally. The convergent parallel design is suitable for this study as it allows me to compare and contrast quantitative statistical results with qualitative findings for corroboration and validation purposes. The four main approaches which are; Phonemic awareness, Read-aloud, Shared Reading and Guided Group Reading were tested through the employment of an intervention administered to individual groups of grade 4 learners applying a particular approach for seven weeks. In the light of the aim of the study, it is clear from data presentation that Read-aloud approach yielded better results in terms of developing and promoting reading skills in the rural intermediate phase. Results of post-intervention comprehension test show that the Read-aloud group had remarkable improvement in terms of the number of learners who could read at an acceptable level. Teachers’ experiences about an effective approach were explored through the questionnaire and interviews; and their responses corroborated findings from learners’ post-intervention comprehension test. Nevertheless, Group Guided Reading should not be ignored as the group that was taught reading using this approach had significant improvement that was corroborated by teacher participants’ responses in both the questionnaire and interviews. Thus, in this study I argue that Read-aloud promote and develop reading skills in the rural intermediate phase.
Thesis (Ph.D. (Language Education)) --University of Limpopo, 2018
Keywords: Teaching; Learning skills; Intermediate phase; Rural primary schools; English language - Study and teaching (Elementary); Early Learning Skills Analysis; Education, Elementary